ANALISIS KINERJA KEUANGAN DAN TINGKAT KESEJAHTERAAN MASYARAKAT KABUPATEN DONGGALA - Marayadnya, I Wayan (Katalogis, 2018)
The study aims to : 1) determine financial performance as represented by independence ratio, Â effectiveness, Â efficiency, harmony, and local revenue of Donggala Regency: 2) determine the level of community welfare as represented by human development indeks of Donggala community.The Study uses secondary data in the form of budget realization report of the APBD of Donggala in the year of 2008-2015 from The Office of Revenue. Financial Administration, and Local Asset of Donggala Regency,while data of human development index is taken from Stastistical Bureau of Donggala from 2010 to 2015. Data analysis used is trend analysis of financial performance includes:a.independence ratio, b. effectiveness ratio, c. efficiency ratio,d. harmony,e. Growth ratio. Meanwhile, indicators of community welfare include: a. Life Expectancy, b. school expectancy and the everage length of school, and c. spending per capita. The results find that:1) financial performance from independence aspect shows very low level of independence;2) effectiveness aspect averagely shows a very high level; 3) efficiency aspect shows a very efficient financial level; 4) harmony aspect of governmental spending shows that the average of indirect and direct spending is quite harmonious; 5) the growth of local revenue shows unsteady even a negative growth. The results on community welfare show that: 1) life expectancy aspect implies an increase on community life ecpectancy; 2) school expectancy and the everage length of school shows an increase; 3) the everage spending per capita shows an increase everagely.